A Logic Programming-Based Approach to QA@CLEF-2005 - Quaresma, Paulo (2012)
In this paper the methodology followed to build a question- answering system for the Portuguese language is described. The system modules are built using computational linguistic tools such as: a Por- tuguese parser based on constraint grammars for the syntactic analysis of the documents sentences and the user questions; a semantic interpreter that rewrites sentences syntactic analysis into discourse representation structures in order to obtain the corpus documents and user questions semantic representation; and finally, a semantic/pragmatic interpreter in order to obtain a knowledge base with facts extracted from the docu- ments using ontologies (general and domain specific) and logic inference. This article includes the system evaluation under the CLEF’05 question and answering track.